Effective Practices to Balance Literacy Instruction in Early Childhood (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Emergent literacy practices have been debated for decades between developmentally appropriate play-based instruction and direct instruction. Recently, accountability and more rigorous standards have placed pressure on early childhood educators to shift literacy instruction to direct teaching with less emphasis on developmentally appropriate play-based instruction. However, emergent literacy skills are multi-faceted, requiring flexible instructional practices. This manuscript addresses the benefits of implementing both play-based and direct instructional practices to balance literacy instruction. Educators should implement a balanced approach to literacy instruction to meet the developmental needs of children and the academic demands of the standards.Keywords: Emergent literacy, balanced literacy instruction, instructional practice, play-based, direct instruction
Keywords: Emergent literacy, balanced literacy instruction, instructional practice, play-based, direct instruction